Fecal thiaminase in feedlot cattle - Hays, T.D.; Brent, B.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fecal thiaminase was measured on 152 feedlot cattle at three locations and on a variety of rations. No animals showed signs of polioencephalomalacia. Thiaminase activities ranged from 0.6 to 430 µmol thiamin destroyed per minute per liter of feces (µmol/min/l). Eighty-two percent of the thiaminase activities were below 20 µmol/min/l, and only 3 percent were less than 2 µmol/min/l. High levels of fecal thiaminase were apparently not related to ration. Thiaminase was detected in all animals studied, but one location had only minimal levels. When high levels of thiaminase were found, the samples were re-assayedt and the enzyme was confirmed to be thiaminase type I. Polioencephalomalaciat a central nervous system disease in ruminants, involves gastrointestinal destruction of thiamint and the creation, through the action of thiaminase I and a cosubstratet of a thiamin analog that inhibits thiamin-requiring metabolic reactions. Our data suggest that substantial numbers of feedlot cattle have the enzyme in their gastrointestinal tracts, but do not develop polioencephalomalacia because the appropriate cosubstrate is absent.
Keywords: Beef; Fecal thiaminase; Cattle; Feedlot